Friday

April 25, 2014

April 25, 2014

Posted by **Chelsi** on Sunday, November 30, 2008 at 7:23pm.

- Math -
**drwls**, Sunday, November 30, 2008 at 7:30pmCall it 3(x^3 + 27).

27 is the cube of three, so one root is x = -3 and the corresponding factor is (x+3). For the other factor, use syntheic division to compute

(x^3+27)/(x+3). That turns out to be

(x^2 -3x + 9). The other roots are complex, so leave it as

3x^3 + 81 = 3(x+3)(x^2 -3x + 9)

**Related Questions**

Math - 1.3x^2+17x+10 2.5y^8-125 3.a^2-2ab-15b^2 *Please help me.You have to ...

math - x^4+3x^3-x^2+6 for x=-3 -3^4+3x-3^3-(-3^2)+6 -81+3x-3^3-(-3^2)+6 81+-24=...

MATH - find the x-intercepts of y=3x^2-6x by factoring y = 3x^2 - 6x Factor out ...

math - How do you factor 3x^2-x-4? thanks in advance How do you factor 3x^2-x-4...

Algebra - I'm not sure how to factor 3x^3-12x^2+3x. I tried separatring the 3x ...

Algebra - I'm trying to solve x^3-3x^2-x+3 is less than zero. Except, I'm not ...

Algebra - Factor: 3x^2 - 27 3x^2-27=0 27+(3x^2-27)=0+27 3x^2=27 (3x^2)/3=27/3 x^...

Math - how do you factor 3x^3-6x^2-24x I know that it becomes 3x(x^2-2x-8), but ...

math - Find the zeroes of the function y=3x^3-3x So I factored that to y=3x(x^2-...

math - factor x^4-3x^3-11x^2+3x+10 completely using the factor theorem.